THE ECONOMIC NATURE OF INTERNATIONAL TOURISM - Tania Gorcheva (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 1970)
Specialized literature does not provide a unanimously accepted definition of the term “tourism”. Regardless of the differences of approach and definition techniques, all definitions are generally based on the need for recreation and achievement of physical and emotional comfort, which are the driving forces for development and execution of various activities to meet those needs. Another approach used to clarify the essence of the term “tourism” allows not only for its social role, but also the economic logic for the development and the management of tourism as an economic activity. This approach, clarifying the essence of the term “tourism” from an economic point of view, allows for the creation of a number of hierarchically related concepts.